The developmental regulation of the human zeta-globin gene in transgenic mice employing beta-galactosidase as a reporter gene. - Pondel, MD; Proudfoot, N; Whitelaw, C; Whitelaw, E (1992)
We have investigated the developmental and tissue specific expression of the human embryonic zeta-globin gene in transgenic mice. A construct containing 550 bp of zeta-globin 5' flanking region, fused to a beta-galactosidase (lacZ) reporter gene and linked to the locus control region (LCR)-like alpha positive regulatory element (alpha PRE) was employed for the production of transgenic mice. Firstly, we compared the number of live born transgenic mice containing this construct to the number of live born transgenic mice containing the entire zeta-globin gene linked to the alpha PRE or the beta LCR. Data showed that 12% of mice generated from eggs injected with zeta-promoter/lacZ/alpha PRE DNA were transgenic compared to only 2% of mice generated from eggs injected with the entire zeta-globin gene linked to the alpha PRE or the beta LCR. The reduced number of live born transgenic mice containing the latter constructs suggests that death of transgenic embryos, possibly due to thalassaemia, may be occurring. X-gal staining of whole embryos containing the lacZ gene revealed that zeta-globin promoter activity was most pronounced at 8.5-9.5 days of development and was restricted to erythroid cells. By 15 days of development, no zeta-globin promoter activity was detected. These results suggest that the alpha PRE can direct high level expression from the zeta-globin promoter and that sequences required for the correct tissue and developmental specific expression of the human zeta-globin gene are present within 550 bp's of 5' flanking region. Sequences within the body of the zeta-globin gene or 3' of the cap site do not appear to be necessary for correct zeta-globin developmental regulation.